Investigation of the effects of combination of acetylsalicylic acid and vitamin c on functions of bovine neutrophils in vitro conditions - Ahmet Levent Baş; Nuri Başpınar; Muammer Elmas; Seyfullah Haliloğlu; Enver Yazar (Eurasian Journal of Veterinary Sciences)
In this study, the effects of combination of acetylsalicylic acid (ASA) and vitamin C at dilferent doses on functions of bovine neutrophils (polymorphonuclear leucoyte/PMNL), and the effects of dilferent ASA concentrations on accumulation of vitamin C in neutrophils were investigated. Neutrophils were obtained from six healthy Holstein-heifers in University Dairy Herd. Phagocytic and microbicidal activity of PMNL were measured with fluorescent microscopic technique and intracellular vitamin C levels were detenııined by spectrophotometer. Intracellular vitamin C levels were incerased by combination of ASA and vitamin C at different concentrations, bul this increase was not statistically significant. Furthenmore, phagocytic and microbicidal activity of PMNL were not statistically changed by these combinations.